2021
DOI: 10.1002/pat.5317
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylamide‐co‐acrylic acid)/chitosan semi‐interpenetrating hydrogel for pressure sensor and controlled drug release

Abstract: With high biocompatibility and pH‐sensitivity, hybrid hydrogels of chitosan (CS) have been widely used in sensor, drug release systems, adsorption, agriculture, and other fields. Herein, a poly(acrylamide‐co‐acrylic acid)/chitosan [P(AM‐co‐AA)/CS] hydrogel with semi‐interpenetrating (semi‐IPN) network was synthesized through in situ copolymerization of acrylamide (AM), N,N′‐methylene‐bisacrylamide (MBAA) and acrylic acid (AA) solution of chitosan using potassium persulfate (KPS) and sodium bisulfite (SBS) as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is noted that the tensile strength of traditional chitosan hydrogel formed by base neutralization is in the range of 0.1-1.25 MPa. [21][22][23] We also found that prolonging the deposition time from 1 to 3 h increased the toughness of the hydrogel tubes. As shown in Fig.…”
mentioning
confidence: 80%
“…It is noted that the tensile strength of traditional chitosan hydrogel formed by base neutralization is in the range of 0.1-1.25 MPa. [21][22][23] We also found that prolonging the deposition time from 1 to 3 h increased the toughness of the hydrogel tubes. As shown in Fig.…”
mentioning
confidence: 80%
“…However, the use of SA hydrogels is limited, since SA is relatively inert when interacting with integrins of mammalian cells [48]; therefore, it is not adhesive for cells. In order to improve these properties, an interpenetrating hydrogel design looks promising [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…As Figure 1B, we chose the common monomer AAm, because its polymer was non‐toxic and commercially available, and the polymer PVA prepared polymer hydrogel. DAAM was used to form acylhydrazone cross‐linked handles 31 . Simply put, it was the free radical polymerization of DAAm and AAm to form a hydrogel in the presence of ADH and borate bonds and hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%